2020
DOI: 10.1093/jofore/fvz072
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive and Evidence-Based Approach to Building and Retaining Gender Diversity within a University Forestry Education Program: A Case Study of SWIFT

Abstract: Retaining women in forestry and other science, technology, engineering, and mathematics fields is a challenge. University education represents a critical point along the forestry pipeline in which women might leave the profession. Concerned with the low number of women graduating with bachelor’s degrees in forestry from the University of Maine’s School of Forest Resources, a group of faculty and students formed Supporting Women in Forestry Today (SWIFT) in 2016. An organization guided by literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…At the University of Michigan, a faculty committee that focused on increasing the hiring of women met with departments and search committees; an analysis limited to a comparison of pre-and post-intervention outcomes found that hires of women in science and engineering more than doubled (Stewart, La Vaque-Manty, and Malley 2004). 6 Soll, Milkman, and Payne (2015) discuss more strategies for reducing bias in evaluations.…”
Section: Graduate Studentsmentioning
confidence: 99%
“…At the University of Michigan, a faculty committee that focused on increasing the hiring of women met with departments and search committees; an analysis limited to a comparison of pre-and post-intervention outcomes found that hires of women in science and engineering more than doubled (Stewart, La Vaque-Manty, and Malley 2004). 6 Soll, Milkman, and Payne (2015) discuss more strategies for reducing bias in evaluations.…”
Section: Graduate Studentsmentioning
confidence: 99%
“…Forest work was seen as hard and dangerous, but as technologies developed, loggers of the 1980s were seen more as competent operators who were mastering machines rather than nature [15,16]. Forest work has evolved further in more recent decades, but these stereotypes of tough and powerful men have perpetuated [11,15,17]. Such narratives can be particularly influential for university students or graduates entering the sector [3,[16][17][18][19][20], potentially reducing the numbers of women entering the workforce.…”
Section: Gender In Forest Research and The Forest Sectormentioning
confidence: 99%
“…Forest work has evolved further in more recent decades, but these stereotypes of tough and powerful men have perpetuated [11,15,17]. Such narratives can be particularly influential for university students or graduates entering the sector [3,[16][17][18][19][20], potentially reducing the numbers of women entering the workforce. Despite these ongoing perceptions, concerns around women in the forest sector are largely absent or inadequately addressed in forestry research journals [11].…”
Section: Gender In Forest Research and The Forest Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Attracting more women should be balanced with retaining women who have been in the sector. Based on a recent study about the importance of women's networks on supporting women's retention in the forestry profession [46], future research can be directed at developing a comprehensive understanding of what is needed to retain women in the forest sector. There is also a need to do research addressing complex gender issues in the forest sector such as sexual harassment and the gender pay gap.…”
Section: Study Limitations and Future Pathwaysmentioning
confidence: 99%